SHAPING STUDENTS' INDEPENDENCE THROUGH PEER EDITING TECHNIQUE TO DEVELOP THEIR WRITING SKILL OF NEWS ITEM TEXT - Rani Autila (Universitas Negeri Padang, 2015)
The students' writing skill of News Item text at grade X5 of SMAN 3 Padang was low. Some of them had difficulties in organization, content, grammar, mechanic, and vocabulary. Then, they really need teachers' correction in every step of their writing process. Therefore, the independent writing should be applied in each part of the writing process. Especially, in editing process the students have to be independent in order to increase their sensitivity on their writing product. Peer editing technique seems to be one of the effective teaching techniques to foster learners' independence in order to develop their writing skill. Therefore, the researcher applied this technique to solve those problems. This is a Classroom Action Research (CAR). The participants of the research were the students of grade X5 of SMAN 3 Padang which consisted of 30 students. This research was conducted in two cycles, which each cycle has four meetings. The researcher was helped by a collaborator. Researcher used writing test, observation checklist and field note, questionnaire and interview as the instruments. The findings showed that the students' writing skill of News Item text are developed through peer editing technique and factors that shaping students' independence through peer editing technique are connecting reading and writing, authentic and interactive activities, and teacher's technique that covered teaching learning process from planning stage to revising stage. In conclusion, applying peer editing technique can shape students' independence to develop their writing skill of News Item text.